2015
DOI: 10.1007/s00262-015-1684-6
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of carcinoembryonic antigen and transforming growth factor-β via their receptors: comparing human and canine cancer

Abstract: There is accumulating evidence that the transforming growth factor beta (TGF-β) and nuclear factor kappa-B (NFκB) pathways are tightly connected and play a key role in malignant transformation in cancer. Immune infiltration by regulatory T- and B-lymphocytes (Tregs, Bregs) has recently gained increased attention for being an important source of TGF-β. There is a plethora of studies examining the pro-tumorigenic functions of carcinoembryonic antigen (CEA), but its receptor CEAR is far less studied. So far, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Recently it has been reported that TGF-β may signal through HNRNPM/CEAR [26]. The authors suggested that NF-kappaB could be a common point between these pathways [26]. Our data also show that MAPK pathway is deregulated by CEA overexpression.…”
Section: Discussionsupporting
confidence: 75%
“…Recently it has been reported that TGF-β may signal through HNRNPM/CEAR [26]. The authors suggested that NF-kappaB could be a common point between these pathways [26]. Our data also show that MAPK pathway is deregulated by CEA overexpression.…”
Section: Discussionsupporting
confidence: 75%
“…TGF‐β elaborated in the malignant tumor microenvironment (TME) binds to the type II receptor (T_RII), promoting hetero‐tetramerization with the type I receptor (T_RI) and increasing the phosphorylation of SMAD3 by activated T_RI. Phosphorylated SMAD3 forms a complex with Co‐Smad (SD4), which promotes translocation into the nucleus and activate expression of target genes, specifically CEACAM6 . Hence, HER2 signaling through the TGF‐β pathway may regulate CEACAM6 expression.…”
Section: Carcinoembryonic Antigen/carcinoembryonic Antigen‐related Cementioning
confidence: 99%
“…Phosphorylated SMAD3 forms a complex with Co-Smad (SD4), which promotes translocation into the nucleus and activate expression of target genes, specifically CEACAM6. 27 Hence, HER2 signaling through the TGF-b pathway may regulate CEACAM6 expression.…”
Section: Transcriptional Regulation Of Carcinoembryonic Antigen/carmentioning
confidence: 99%
“…However, it remains unclear whether STAT3 is involved in TGFβ-regulated VSMC contractile and proinflammatory gene programs. In addition, TGFβ signaling has been shown to crosstalk with nuclear factor κB (NF-κB) pathway [3237], but the interplay of these two integral pathways and the resulted functional consequences upon the activation of TGFβ cascade in VSMCs are not fully unraveled.…”
Section: Introductionmentioning
confidence: 99%